Tingkat Kepuasan Pengguna Terhadap Layanan Perpustakan Kota Lubuk Linggau - Hardi Mulyono; Yulpa Rabeta; Endri Mike Setiawan (Forum Kerjasama Pendidikan Tinggi, 2021)
This study aims to determine the effect of training and competence on employee performance in the Ministry of ART / BPN, Musi Rawas Land Office. The number of research samples was 31 people. Data taken from direct respondents using a questionnaire instrument. Data analysis using quantitative data analysis, while the data analysis techniques used in this study are: simple linear regression, multiple linear regression. Processing data using the SPSS 22 application. The results of this study provide the following conclusions: (a) the results of the study show that training has a partial effect on employee performance. (b) the results of the study show that competence partially has an influence on employee performance. (c) the research results show that there is a significant effect simultaneously between Training and Competence on Employee Performance at the Ministry of ATR / BPN, Musi Rawas Land Office